Debt Management Performance Assessment : Solomon Islands - World Bank (Washington, DC, 2013)
From February 19 to 28, 2009, a World Bank team undertook a debt management performance assessment (DeMPA) mission to Honiara, Solomon Islands. The objective was to undertake a comprehensive assessment of debt management functions applying the DeMPA tool. The assessment reveals that the Solomon Islands meets the minimum requirements for effective debt management performance as specified by the DeMPA tool on the legal framework, coordination with monetary policy, and debt reporting. While taking note of substantial efforts to improve performance in a number of areas, the assessment also found that the Solomon Islands does not meet the minimum requirements for the indicators assessing the debt management strategy, managerial structure, coordination with fiscal policy, domestic borrowing, cash flow forecasting and cash balance management, debt records, and debt recording. The mission also identified the following areas that require improvement and could be considered priorities for capacity building and reform: evaluation of debt management operations; auditing; external borrowing; loan guarantees, on-lending and debt-related transactions; debt administration and data security, and; segregation of duties, staff capacity and business continuity.